Myocardial ketone body utilization in patients with heart failure: The impact of oral ketone ester - Monzo, Luca; Sedlacek, Kamil; Hromanikova, Katarina; Tomanova, Lucie; Borlaug, Barry A; Jabor, Antonin; Kautzner, Josef; Melenovsky, Vojtech (Metabolism: clinical and experimental, 2021)
AIMS: Upregulation of ketone body (β-hydroxybutyrate, βHB) utilization has been documented in human end-stage heart failure (HF), but is unclear if this is due to intrinsic cardiac metabolic remodeling or a HF-related catabolic state. This study sought to evaluate the maximal ketone body utilization capacity and its determinants in controls and in patients with moderate HF and reduced ejection fraction (HFrEF). METHODS AND RESULTS: 19 HFrEF patients and 9 controls underwent sampling from the arterial circulation (A) and coronary sinus (CS) to measure transmyocardial extraction of energy-providing substrates and oxygen. In a separate experiment, measurements were performed 80-min after oral administration of 25 g of ketone ester (KE, (R)-3-hydroxybutyl(R)-3-hydroxybutyrate) drink in 11 HFrEF and 6 control subjects. There were no statistically significant differences in fasting substrate levels and fractional extractions between HF and controls. Administration of KE increased βHB by 12.9-fold, revealing an increased ability to utilize ketones in HFrEF as compared to controls (fractional extraction, FE%: 52 vs 39%, p = 0.035). βHB FE% correlated directly with βHB myocardial delivery (r = 0.90), LV mass (r = 0.56), LV diameter (r = 0.65) and inversely with LV EF (-0.59) (all p < 0.05). βHB FE% positively correlated with lactate FE% (p < 0.01), but not with FFA or glucose FE%, arguing against substrate competition. CONCLUSIONS: Acute nutritional ketosis enhances βHB extraction in patients with HFrEF compared to controls, and this enhancement correlates with degree of cardiac dysfunction and remodeling. Data suggest that subclinical metabolic remodeling occurs early in HF progression. Further studies are needed to determine whether exogenous ketones may have a potential therapeutic role.
Keywords: senioři; estery; senioři nad 80 let; ketolátky; Middle Aged; mužské pohlaví; β-hydroxybutyrate; Energy Metabolism; Ketone ester; Heart failure; Exogenous ketones; Fasting; β-oxidation; omezení příjmu potravy; Aged, 80 and over; energetický metabolismus; ženské pohlaví; myokard; Humans; Myocardium; lidé středního věku; srdeční selhání; Ketone Bodies; Esters; Myocardial metabolism; Female; Aged; Heart Failure; lidé; Male